A qualidade da escola pública APESAR do Simave - Souza, Alesandra Ferreira Bento (2016)
This study is part of a larger research entitled “Quality production from the Policy of systemic evaluation in public basic schools of Uberlândia and Ituiutaba. Minas Gerais State, Brazil”. It aimed to understand how the systemic evaluation has contributed to build Education quality. As a cut for Mastership dissertation, we aimed to identify and analyze how the systemic evaluation in Minas Gerais has influenced the Pedagogical Work Organization (PWO) od a public basic school which is considered by external and internal community as a quality institution. We seek to identify which kind of changes the evaluation named SIMAVE1 has induced and whether they have produced education quality indeed. We also dialogued to the protagonists of the three schools who took part of the research (teachers, students and families) in order to identify how they have understood such a thing as Education quality. It is a qualitative study that used documental, bibliographic and field researches. We also used observation, written and photographic records on daily school, interviews and questionnaires to the participants. Among the results, we faced a political and school scenario that states increasingly conceptions in favor of neoliberal ideas which runs through the large-scale assessments and tend to reduce the Pedagogical Work Organization to prepare a kind of learning what is possible to measure. As an impact of policy evaluation, when we look at the school ground, we perceive subjects suffering to extend their results on standardized tests. The design established in these valuation policies on a large scale in progress, although being presented as a complement of the internal evaluation, on the contrary, impacts it, to reframe the evaluation of the training design itself. However, we observed that beyond the influences of External Evaluation, the studied school keep in its PWO some actions with high potentiality for a formation of social quality. Concerning to the subjects’ perception of how they understand Education quality, they reveal, in one hand, a kind of appropriation of official speeches legitimizing the proficiency index as school quality indicator, but, on the other hand, we also faced a set of multiple indicators proposed by various theoretical and empirically formulated by the subjects of the schools, quality results which, in turn, is not restricted to the proficiency produced by external testing, but refer to some elements such as teacher valorization, professional commitment to the student’s development, adequate infrastructure in schools, teaching projects and learning, interpersonal relationship and so one. We understand that these indicators can highlight on socially relevant contribution to a quality education proposal molded from the school materiality.